Penerapan Prinsip-Prinsip Good Corporate Governance (GCG) Dalam Pengelolaan Lingkungan Industri Pengecoran Logam Studi Kasus Perkampungan Industri Kecil (PIK) Desa Kebasen Kecamatan Talang Kabupaten Tegal - Almas Lathuf Assyura; edi santosa; achmad taufiq (Journal of Politic and Government Studies, 2018)
ABSTRACTDisposal of waste results from industrial activities can cause pollution if not managed properly. Perkampungan Industri Kecil (PIK) is an area of the metal casting industry that produces metal waste containing hazardous and toxic materials. Industrial environmental management is needed to prevent pollution of waste that can have an impact on the environment. In the environmental management industry in PIK apply the policy principles of Good Corporate Governance (GCG) so that the management can be known how much adherence to the rules.This study uses a mixture(mixing)between qualitative and quantitative research using data observation, interviews, documentation, and a questionnaire to explain in detail the real situation. In this study, informants taken include the Environment Agency Tegal regency and PT LUT Son Solder as the manager of PIK as well as in-depth interviews to the public, while the questionnaire given to the metalworkers using techniques Proportional purposive sampling is to apply specific criteria in accordance with the research purposes.The application of corporate governance principles is done using the five principles of transparency, accountability, responsibility, independence and fairness. This implementation is done according to Law No. 23 of 2997 on Environmental Management. Based on research conducted showed that GCG principles have been applied in the management of the environment and the level of compliance with environmental management through GCG is abiding by a percentage of 86.8%. As well as many obstacles in the form of limited human resources in implementation.The recommendations given in this study were (1) the importance of socialization legislation governing industrial and environmental management; (2) simulation of the craftsman regarding cleaner production in metal processing activities at PIK; (3) imposing sanctions on the one who has not executed correctly K3; (4) the application of the principles of good corporate governance to all stakeholders, including metalworkers. Keywords: Principles of Good Corporate Governance, Environmental Management Industry, Industrial Area, B3